Influence of school leadership culture on students’ academic performance in mixed public secondary schools in Gucha region Kisii county - MACHARIA, JOSEPH; Atieno, Caroline; Kwaba, Jacob Gekonge (International Journal for Innovation Education and Research, 2023)
A study in social science rekindles a link between organizational culture and its effectiveness. Effective school has also come up with many attributes that were evident in schools that seem to contribute to academic achievement. The aim of this study was to investigate the influence of school culture and its influence on students’ academic performance at KCSE level. The objectives of this study were; to examine the influence of school leadership on students’ academic performance and to assess the influence of school routines on students’ academic performance in mixed public secondary schools in Gucha region Kisii County. The study was guided by Edgar Schein’s organizational culture theory and Effective schools’ theory. Mixed methodology and concurrent triangulation research design guided the study. Qualitative and quantitative data was collected, analyzed and results merged for discussions and conclusions. The target population included 37 principals, 650 teachers and 15,865 students yielding 16, 552 participants. Purposeful sampling raised 17 principals, 150 teachers were randomly selected and 300 students sampled through stratified random sampling. 467 respondents were sampled for study. Questionnaires were given to teachers and students, interview guide was used by the researcher and interview guide was used by the researcher when interviewing the principals. The instruments were piloted on 10% of the sample size. Validity of the instruments was ascertained through expert judgment and reliability was attained through test re-test and calculated using statistical package for social sciences (SPSS) version 24 and Cronbach alpha technique. Internal consistency of 0.7 was obtained. Credibility of the instruments was ascertained through data triangulation to ensure that findings were dependable at every step, well-articulated and detailed. Qualitative data was analyzed thematically and presented in narrative form while quantitative data was analyzed using descriptive and inferential statistics. Linear regression was carried out and findings presented using tables and graphs. The study concluded that influence of school routines on students’ academic performance, leading by example had a strong positive correlation of .539**indicating that strengthening school culture help in improving academic performance Gucha region, Kisii County. The study recommended that leaders of secondary schools should lead by example and promote a positive performance culture in schools.